2022
DOI: 10.1177/00846724221133455
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19, death depression and death anxiety: Religious coping as a mediator

Abstract: The COVID-19 pandemic has affected the well-being and mental health of populations worldwide. This study sought to examine whether religious coping mediated the relationship between COVID-19-related fear and death distress. We administered an online survey to 390 adult participants (66.15% females; Mage = 30.85 ± 10.19 years) across Turkey. Participants completed a series of questionnaires measuring the fear they had experienced during the COVID-19 pandemic, their levels of religious coping and their levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…Similar findings were observed in our systematic review and meta-analysis in which the pooled event rate of psychological problems was 32% (95% CI: 28%, 36%; I 2 = 99.85). Our results also partially supported the hypothesis that the event rates of psychological and behavioral problems were different among countries with different economic statuses ( 100 102 ). In the subgroup analysis, there were significant differences in the event rates between high-income and upper middle-income countries and between upper middle-income and lower middle-income countries for psychological problems (both p < 0.001).…”
Section: Discussionsupporting
confidence: 85%
“…Similar findings were observed in our systematic review and meta-analysis in which the pooled event rate of psychological problems was 32% (95% CI: 28%, 36%; I 2 = 99.85). Our results also partially supported the hypothesis that the event rates of psychological and behavioral problems were different among countries with different economic statuses ( 100 102 ). In the subgroup analysis, there were significant differences in the event rates between high-income and upper middle-income countries and between upper middle-income and lower middle-income countries for psychological problems (both p < 0.001).…”
Section: Discussionsupporting
confidence: 85%
“…This includes perceiving the virus as a predetermined destiny and a test from God, as well as employing religion to manage the adverse effects of the pandemic. Furthermore, Kızılgeçit and Yıldırım (2022) demonstrated the significance of religious coping methods and their moderating functions in the relationship between fear of COVID-19 and death anxiety in young Turkish individuals. However, the literature still needs more inquiries on if COVID-19 has permanently increased the use of religion among people or if it was just a short-term reaction to deal with the first shocking impacts of the pandemic.…”
Section: Religiosity As a Coping Mechanism For The Negative Impacts O...mentioning
confidence: 95%
“…Religion has emerged as a strong coping mechanism that has been employed by many people around the world during the pandemic, and numerous studies have been conducted to investigate the relationship between religion and COVID-19. Several studies around the world (e.g., Bentzen, 2021;Kowalczyk et al, 2020;Iyer et al, 2024) and in Turkey (e.g., Kalgı, 2021;Eryiğit and Başak, 2021;Bulut and Koç, 2022;Kızılgeçit and Yıldırım, 2022) (these studies will be discussed comprehensively in the next sections) have clearly revealed that religion has been employed to cope with the negative impacts of COVID-19. However, there is still need for more inquiries that examine how COVID-19 and death anxiety impacted individuals' religious lives in the post-COVID-19 period.…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, NRC does not only fail to relieve stress but can even elicit greater unpleasant emotions such as agitation and fury. This dimension of religious coping has been found to be positively associated with anxiety and depressive symptoms, as well as with poor health-related quality of life across various life domains ( 20 , 46 ).…”
Section: Introductionmentioning
confidence: 99%